(untitled) - Sullivan, Chad (Indianapolis, 2005)
Cisco Security Agent is the first book to explore the features and benefits of this powerful host IPS product. Divided into seven parts, the book provides a detailed overview of Cisco Security Agent features and deployment scenarios. Part I covers the importance of endpoint security. Part II examines the basic components of the Cisco Security Agent architecture. Part III addresses agent installation and local use. Part IV discusses the Cisco Security Agent management console’s reporting and monitoring capabilities. Part V covers advanced Cisco Security Agent analysis features. Part VI covers Cisco Security Agent policy, implementation, and management. Part VII presents additional installation and management information.
Keywords: Computer networks; Security measures